Evaluation of micronuclei frequency in Tradescantia pallida pollen mother cells treated with ethanolic extracts isolated from Cryptocarya mandioccana, Cryptocarya moschata and Pterogyne nitens - De Oliveira, Aline Miranda [UNESP]; Caliri, Camila Milva [UNESP]; Regasini, Luis Octávio [UNESP]; Telascrea, Marcelo [UNESP]; Peron, Mariana Cristina Caloni [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Dos Santos, André Gonzaga [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Cavalherio, Alberto José [UNESP]; Soares, Christiane Pienna [UNESP] (My University, 2007)
Although herbal extracts contain several classes of compounds with pharmacological activity, they also present toxic substances with mutagenic effects. The aim of the present study was to verify the mutagenicity of Cryptocarya moschata, Cryptocarya mandioccana and Pterogyne nitens using micronucleus assay in pollen mother cells (tetrads) in Tradescantia pallida (Trad-MCN). T. pallida inflorescences were treated with different concentrations of ethanolic extracts from the selected plant species. For C. mandioccana C. moschata and P. nitens, Trad-MCN assays were carried out simultaneoulsly, followed by positive control (formaldehyde 10000 ppm), negative control (Hoagland's solution), and vehicle control (Tween 20 20% or DMSO 3%). MCN present in tetrads were quantified in 300 tetrads/inflorescence and the mean (%) and standard error (SE) were established for at least 10 inflorescences per treatment. The extracts demonstrated dose response mutagenicity (clastogenic/aneugenic effects), respectively, C. mandioccana (0.5, 1.0 and 2.0 mg/mL) and P. nitens (1.0 and 2.0 mg/mL) However, no mutagenic effect was observed to C. moschata at the concentrations evaluated in the present study. We can conclude that the C. mandioccana and P. nitens extracts demonstrated clastogenic/aneugenic effects in highest concentrations whereas C. moschata extract did not demonstrate the same effect. © 2006 Sociedade Brasileira de Toxicologia.
Keywords: Aneugenic; Clastogenic; Cryptocarya mandioccana; Cryptocarya moschata; Pterogyne nitens; Trad-MCN